Evolutionary trajectory and characteristics of Mpox virus in 2023 based on a large-scale genomic surveillance in Shenzhen, China - Zhang, Shengjie; Wang, Fuxiang; Peng, Yun; Gong, Xiaohua; Fan, Guohao; Lin, Yuanlong; Yang, Liuqing; Shen, Liang; Niu, Shiyu; Liu, Jiexiang; Yin, Yue; Yuan, Jing; et al. (Nature communications, 2024)
The global epidemic of Mpox virus (MPXV) continues, and a local outbreak has occurred in Shenzhen city since June 2023. Herein, the evolutionary trajectory and characteristics of MPXV in 2023 were analyzed using 92 MPXV sequences from the Shenzhen outbreak and the available genomes from GISAID and GenBank databases. Phylogenetic tracing of the 92 MPXVs suggests that MPXVs in Shenzhen may have multiple sources of importation, and two main transmission chains have been established. The combination of phylogenetic relationships, epidemiological features, and mutation characteristics supports the emergence of a new lineage C.1.1. Together with the B.1 lineage diverging from the A.1 lineage, C.1.1 lineage diverging from the C.1 lineage may serve as another significant evolutionary events of MPXV. Moreover, increasing apolipoprotein B mRNA-editing catalytic polypeptide-like 3 (APOBEC3) related mutations, higher rate of missense mutations, and less mutations in the non-coding regions have been shown during MPXV evolution. Host regulation proteins of MPXV have accumulated considerable amino acid mutations since the B.1 lineage, and a lineage-defining APOBEC3-related mutation that disrupts the N2L gene encoding a viral innate immune modulator has been identified in the C.1.1 lineage. In summary, our study provides compelling evidence for the ongoing evolution of MPXV with specific features. Mpox virus has spread globally since 2022 with cases in many previously non-endemic countries including China. Here, the authors describe the genomic epidemiology of the first local outbreak in Shenzhen, China, including 92 cases reported from June–Oct 2023.